Brand Creation Training as Product Identity for Fashion Category in Karangayu Market, West Semarang Subdistrict, Semarang City, Central Java - Muhamad Syaeful Anwar; Lely Afiati; Liesta Verawati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
MSMEs in Indonesia have experienced positive growth over the past three years and are one of the largest contributors to Indonesia’s GDP. In Semarang, especially in the fashion sector at Karangayu Market, many sellers do not yet have a clear brand identity, making it difficult to compete with competitors. Understanding the importance of brand identity is essential to increase competitiveness and attract more consumers. This research aims to enhance the understanding and skills of sellers in Karangayu Market in creating and utilizing brands as identity for their fashion products. The community service activity was conducted on Thursday, March 7, 2024, with partners from the Association of Traders and Services of Karangayu Market, Semarang City. The stages of community service included location surveys, problem identification, presentations on the importance of brand identity, brand creation training, and activity evaluations to ensure the effectiveness and sustainability of the actions taken. This training resulted in an enhanced understanding and skillset among the traders regarding the significance of brand identity. Training participants, such as Dhea and Ana, successfully created brand identities that aligned with their business philosophies and personalities. The established brand identities are expected to be implemented on partner products, contributing to increased sales and consumer awareness. This brand identity creation training effectively assisted Pasar Karangayu traders in establishing strong brand identities. The implementation of this community service activity not only enhanced the traders’ skills but is also anticipated to be implemented sustainably to support the success of MSMEs in the fashion sector. A strong brand identity will aid consumers in recognizing and differentiating products from competitors, thereby expanding market reach and enhancing business competitiveness.